Integration Of Green Monetary and Green Fiscal Policies In Supporting The Effectiveness Of Economic Transformation Towards Development Sustainable In Indonesia - Putri Valentine; Sabilayana Sabilayana; Rusiadi Rusiadi; Suhendi Suhendi; Lia Nazliana Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine Renewable Energy, Emission Intensity, Life Expectancy, and Unemployment Rate on Gross National Income (GNI) in Estonia, Finland, Germany, Hungary, and Norway. The variables in this research are Renewable Energy, Emission Intensity, Life Expectancy, and Unemployment Rate as independent variables, while the Gross National Income variable is the dependent variable. This research uses secondary data taken from the OECD from 2011-2023. The data analysis technique used is the Autoregressive Distributed Lag (ARDL) panel. The research results from the ARDL model analysis show that the country that is able to become a leading indicator for the stability of the GNI rate is only Norway. This is because all the variables or indicators in the research, namely (Renewable Energy, Life Expectancy, and Unemployment Rate), this country has a significant effect on GNI. while the Emission Intensity variable does not have a significant effect on GNI. If we look at the stability of the short run and long run, the Unemployment Rate variable, both in the short and long term, significantly controls the stability of GNI.